2019
DOI: 10.1128/msphere.00262-19
|View full text |Cite
|
Sign up to set email alerts
|

Disarming Pore-Forming Toxins with Biomimetic Nanosponges in Intraocular Infections

Abstract: Intraocular infections are prevalent after traumatic injuries or after common ocular surgeries. Infections cause inflammation that can damage the retina and architecture of the eye, often resulting in poor visual outcomes. Severe cases may result in blindness or require enucleation of the eye. Treatments for intraocular infections include intravitreal antibiotics and corticosteroids or surgical vitrectomy in serious cases. The increase in multidrug-resistant infections calls for novel treatment options. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…These nanoparticles, termed nanosponges, neutralized α-toxin and reduced hemolytic activity in vitro, protected mice from developing staphylococcal α-toxin induced skin lesions, and decreased mortality after systemic injection of a lethal dose of α-toxin [91]. In a mouse model of S. aureus endophthalmitis, Coburn et al [92] reported that intraocular injection of nanosponges alone following infection did not result in improved retinal function compared to untreated mice. However, injection of nanosponges in conjunction with the fourth-generation fluoroquinolone gatifloxacin resulted in decreased inflammation, less damage to the retinal architecture, and significantly improved retinal function compared to untreated or gatifloxacin only treated mice following intraocular infection with an MRSA ocular isolate [92].…”
Section: Membrane-damaging Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanoparticles, termed nanosponges, neutralized α-toxin and reduced hemolytic activity in vitro, protected mice from developing staphylococcal α-toxin induced skin lesions, and decreased mortality after systemic injection of a lethal dose of α-toxin [91]. In a mouse model of S. aureus endophthalmitis, Coburn et al [92] reported that intraocular injection of nanosponges alone following infection did not result in improved retinal function compared to untreated mice. However, injection of nanosponges in conjunction with the fourth-generation fluoroquinolone gatifloxacin resulted in decreased inflammation, less damage to the retinal architecture, and significantly improved retinal function compared to untreated or gatifloxacin only treated mice following intraocular infection with an MRSA ocular isolate [92].…”
Section: Membrane-damaging Toxinsmentioning
confidence: 99%
“…In a mouse model of S. aureus endophthalmitis, Coburn et al [92] reported that intraocular injection of nanosponges alone following infection did not result in improved retinal function compared to untreated mice. However, injection of nanosponges in conjunction with the fourth-generation fluoroquinolone gatifloxacin resulted in decreased inflammation, less damage to the retinal architecture, and significantly improved retinal function compared to untreated or gatifloxacin only treated mice following intraocular infection with an MRSA ocular isolate [92]. These studies suggested that nanosponges might be a viable adjunctive therapy for intraocular infections caused by S. aureus .…”
Section: Membrane-damaging Toxinsmentioning
confidence: 99%
“…Our findings suggest that the InhAs may facilitate intraocular bacterial growth by producing an environment more conducive to persistence. Current therapeutics are relatively ineffective in treating Bacillus endophthalmitis [1,[9][10][11][59][60][61][62][63], and due to its rapidly blinding course, Bacillus endophthalmitis requires early and precise treatment [62,63]. Treatment strategies for Bacillus and other types of endophthalmitis should be based on knowledge of the virulence factors that contribute to disease pathogenesis.…”
Section: Retained Retinal Function In Eyes Infected With Bacillus Lacmentioning
confidence: 99%
“…Every 2 hours, 20-μL aliquots were track diluted in PBS and plated onto BHI agar plates, and counted after 24 hours [2,6,21,23,26,65,[65][66][67]. Values are expressed in percent hemolysis relative to a 100% lysis control, as previously described [16,19,26,61,68].Values represent the means ± SD of two independent experiments.…”
Section: Bacterial Growth Curvesmentioning
confidence: 99%
“…From a treatment standpoint, Bacillus endophthalmitis cases are difficult and are often associated with worse patient outcomes than infections caused by other pathogenic species. 6,[8][9][10][11] The pathogenicity of Bacillus endophthalmitis is linked to the inflammogenic potential of the bacterial cell wall and the secretion of toxins and enzymes. [12][13][14][15][16][17][18] The severe nature of Bacillus endophthalmitis requires prompt and rapid therapy to halt disease progression.…”
mentioning
confidence: 99%